Pilot assisted readout for passive memristor crossbars. (August 2016) - Naous, Rawan; Affan Zidan, Mohammad; Sultan, Ahmed; Nabil Salama, Khaled
Abstract: The high demands for performance and energy efficiency pose significant challenges for computational systems. Memristor-based crossbar architectures are actively considered as vital rivals for the traditional solutions. Nonetheless, density and energy driven passive array structures, that lack a switching control per cell, suffer from sneak paths that limit the range of accurate operation of the crossbar array. In this paper, the crossbar array is treated as a communication channel with added distortion to represent the sneak current. Estimation techniques based on preset pilots are utilized to alleviate the distorting effects and enhance the system throughput. A two dimensional setting of these reference points leads to an accurate estimation of and compensation for the sneak paths effects. Thereby a comprehensive technique is presented that boosts the performance and accommodates functional metrics of speed, energy efficiency, accuracy and density all within a single envelope. SPICE simulations cover the data patterns dependencies, the non-linearity impact, and the crossbar distortion. It offers a further validation, from several aspects, on the reliable operation attained with the complete separation of the high and low bits regions.